Pengaruh Pendidikan Ekonomi Terhadap Perilaku Konsumtif Remaja: Perspektif Manajemen Keuangan Pribadi - Arniati Arniati; Siti Marhumi (CV. Eureka Murakabi Abadi, 2025)
Adolescent consumer behavior is one of the challenges in character building of the younger generation, especially in the digital era that is full of the influence of social media and easy access to consumption. This study aims to analyze the effect of economic education on adolescent consumer behavior with a personal financial management approach. The method used is a quantitative approach with a survey technique on high school students in several schools in Indonesia. Data were analyzed using multiple linear regression to determine the relationship between economic education and consumer behavior with personal financial management variables as mediating variables. The results of the study indicate that economic education has a significant effect on reducing adolescent consumer behavior, both directly and indirectly through strengthening personal financial management skills, such as budget planning, spending control, and rational financial decision making. These findings indicate the importance of integrating personal financial management materials into the economic education curriculum to form healthy financial behavior among adolescents. This study contributes to the development of more applicable and adaptive educational strategies in equipping the younger generation with financial skills that are relevant to the challenges of the times.